SOX8 Knockdown Overcomes Enzalutamide Resistance in Castration-Resistant Prostate Cancer by Inhibiting the Notch Signaling Pathway. (6th October 2022) - Du, Zhongbo; Chen, Xiaobin; Zhu, Pingyu; Sun, Wei; Lv, Qi; Cheng, Shulin; Yang, Xuesong; Yu, Xiaodong
Abstract : Castration-resistant prostate cancer (CRPC) is still challenging to treat. Dissatisfaction with androgen signal-targeted therapy forces people to look for other treatment strategies. Therefore, this study is aimed at exploring the role of SOX8/Notch signaling in CRPC. The upregulation of SOX8, Notch4, and Hes5 indicated a poor progression-free survival (PFS) in CRPC patients. The expression of these proteins was also upregulated in enzalutamide-resistant LNCaP cells (Enza-R). Moreover, knocking down SOX8 inhibited malignant biological behaviors and decreased the activation of Notch signaling in Enza-R cells. Importantly, knocking down SOX8 obviously reversed the enzalutamide resistance in Enza-R cells, while RO0429097 (a γ secretase inhibitor inactivates Notch signaling) exerted similar effects. At last, we found that both SOX8 knockdown and/or RO0429097 suppressed tumor growth and bone metastasis in vivo . Altogether, our study indicated that the SOX8/Notch signaling is involved in CRPC and that these enzymes are possible targets to develop novel treatment for CRPC.